Case reportApplication of native prick test in diagnosis of bed bug allergy - Ukleja-Sokołowska, Natalia; Sokołowski, Łukasz; Gawrońska-Ukleja, Ewa; Bartuzi, Zbigniew (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2013)
The aim of the study was case report of the patient with systemic reaction after a bed bug ( Cimex lectularius ) bite. A 23-year-old female, previously healthy, reports systemic reaction, including rash on her corpus and limbs, itching, nausea, conciseness disorder, forcing her to call the ambulance. The interview revealed that the bed bug occurs in the patient’s apartment. A prick-by-prick test with bed bug excretion was made. The skin test with native allergen was strongly positive (histamine 5 mm/5 mm, prick-by-prick 12 mm/8 mm). The prick-by-prick test was useful in objective confirmation of the source of symptoms.